Postmortem Sampling of the Pancreas for Histological Examination: What Is the Optimum Cut-Off Time? - Siriwardana, Rohan Chaminda; Deen, Kamel Ismile; Hevawesenthi, Janaki (JOP. Journal of the Pancreas, 2016)
No abstract available. Image: Quality of microscopic specimens according to time after death.